It's not over structural drivers of the global economic crisis - Rohit (Oxford : Oxford University Press, 2013)
This book argues that while deregulation definitely aided it, it cannot be the basis for the crisis. Instead of concentrating on the financial side alone, this work attempts to bring the real economy into focus by using a heterodox framework which challenges the current dominant thinking in the discipline. It examines, theoretically and empirically, whether increased income and wealth inequalities and business concentration contributed to the instability in the US economy.
Description based on online resource; title from home page (viewed on Jan. 4, 2013).
Includes bibliographical references and index.
Keywords: Global Financial Crisis, 2008-2009.